2013
DOI: 10.1128/iai.00869-13
|View full text |Cite
|
Sign up to set email alerts
|

In VivoPhysiological and Transcriptional Profiling Reveals Host Responses to Clostridium difficile Toxin A and Toxin B

Abstract: Toxin A (TcdA) and toxin B (TcdB) of Clostridium difficile cause gross pathological changes (e.g., inflammation, secretion, and diarrhea) in the infected host, yet the molecular and cellular pathways leading to observed host responses are poorly understood. To address this gap, we evaluated the effects of single doses of TcdA and/or TcdB injected into the ceca of mice, and several endpoints were analyzed, including tissue pathology, neutrophil infiltration, epithelial-layer gene expression, chemokine levels, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 51 publications
3
33
0
Order By: Relevance
“…1 and 3). This further supports that TcdA was more potent than TcdB in this model, although the host transcriptional responses to TcdA and TcdB are reportedly similar [43]. But the rapid death caused by TcdA may also be due to shock; however, a few of the mice treated with the highest dose of TcdA quickly produced watery diarrhea which may have flushed out some of the excess toxin and allowed them to survive for a few extra hours, but they still succumbed to death in less than 48 h like those receiving a fifth of the dose.…”
Section: Discussionsupporting
confidence: 66%
“…1 and 3). This further supports that TcdA was more potent than TcdB in this model, although the host transcriptional responses to TcdA and TcdB are reportedly similar [43]. But the rapid death caused by TcdA may also be due to shock; however, a few of the mice treated with the highest dose of TcdA quickly produced watery diarrhea which may have flushed out some of the excess toxin and allowed them to survive for a few extra hours, but they still succumbed to death in less than 48 h like those receiving a fifth of the dose.…”
Section: Discussionsupporting
confidence: 66%
“…Neutrophils isolated from Il22 −/− and WT mice showed a similar bactericidal activity (Figure S5B), indicating that IL-22 does not affect the bactericidal activity of neutrophils. To further study the immune responses elicited by IL-22, we reviewed the GEO dataset (accession GDS3226 and GSE44091) of gene expression in IL-22-treated or TcdA and TcdB toxins-treated murine intestines (Zheng et al ., 2008; D‧Auria et al ., 2013). In addition to genes known to be induced by IL-22, such as S100 proteins and acute phase proteins (Liang et al ., 2010; Sonnenberg et al ., 2012), analysis of the datasets revealed increased expression of complement factor C3 in IL-22- and TcdA/TcdB toxins-treated mice (Figure S5 C and D).…”
Section: Resultsmentioning
confidence: 99%
“…We further used acute murine CDI model 9 In summary, by using two independent animal intestinal disease models, we consistently demonstrated that TcdB in vivo potency is critically dependent on the glucosyltransferase activity. These results are consistent with our previous studies using systemic toxemia model 10,11 .…”
Section: Induction Of Acute Murine CDI In a Cecum Toxin Injection Modelmentioning
confidence: 85%